URGENSI PENDIDIKAN KARAKTER DAN NASIONALISME BAGI ANAK USIA DINI - Setyowati, Eriva; Ningrum, Mallevi Agustin (PG PAUD Universitas Negeri Surabaya, 2020)
Character education is an important and strategic step in rebuilding the identity of individual nations and countries. Character education must involve all parties such as parents, closest family, school, and community. Where human character is the result of the attraction between good and bad values in the form of positive and negative energy in oneself. Early childhood needs extra understanding and habituation because early childhood is the next generation of young people. So that in character education, children are taught to have noble characters who love and boast of their nation and country. One of the efforts from various groups, both government and society is done by developing children's soft skills education from an early age.